ПРИПОВЕДАЧКА ПОЕТИКА И КЊИЖЕВНА ЕСТЕТИКА МИЛАНА КАШАНИНА - Jana M. Aleksić (Philological Studies, 2019)
The paper examines and analyzes the narrative and novelistic opus of Milan Kašanin, the Serbian public is better known for his literary and artistic criticism. The subject of analysis were the collection of his short stories Matins and vigils (1925, 1926), Lovers (1928), In the Shadow of Glory (1961) and his novels Three shirts man (1930), Drunk country (1932), Apparition (1981). The article problematizes the so far in criticizing the widespread realistic determination of his poetic framework and hypothesis about the poetic pluralism, stylistic and linguistic diversity of Kašanin`s prose. In order to clarify and shape the narrative and character immanent poetics of this author, we highlighted the different narrative strategies and techniques he had used, dominant spiritual and conceptual, thematic and motifs and stylistic-linguistic aspects of his prose works, as well as correspondence with his aesthetic vision, which is explicitly and implicitly had been exposed in his literary and artistic critical texts and monographs.